Aristotle Dictionary. - Kiernan, Thomas (Philosophical Library/Open Road, 2018)
At long last, a comprehensive tool in English for a better understanding of the most basic terms in Aristotle's philosophy. Interested readers, students, and scholars of philosophy and of the general intellectual background of Western culture need no longer be handicapped by a lack of knowledge of Greek and Latin. A careful comparison of the original Greek, Medieval, and Renaissance Latin translations and a reappraisal of English usage make Aristotle Dictionary a definitive source for the precise grasp of what has been the historical Aristotle as far as the documents permit one to judge. A lengthy introduction by Professor Theodore E. James presents an analysis of the major works of Aristotle.